The coming of the Italian-Ethiopian war - Baer, George W. (Harvard Univ. Pr, 1967)
Analysis of the causes of the Italian-Ethiopian War of 1936, Mussolini's plans for invasion and Ethiopia's defense, and the European aftermath.